The relationship between fundamental motor skills and executive function in children: a stratified analysis by age and sex - Kong, Chuifeng; Cai, Yujun; Li, Kai; Wang, Zisu; Wen, Xili; Zhang, Xinmiao (Frontiers in Psychology, 2025)
ObjectiveThis study aimed to systematically examine the relationship between fundamental motor skills (FMS) and executive function (EF) in Chinese children aged 3 to 10 years. The study specifically focused on age and sex differences, as well as the associations between subcomponents of FMS and EF, to provide empirical evidence for research and intervention strategies targeting motor-cognitive integration in child development.MethodsA cross-sectional study design was employed, utilizing multi-stage stratified cluster sampling to recruit 2,179 children aged 3 to 10 years from eight cities across four eastern provinces in China (Jiangsu, Zhejiang, Anhui, and Shandong). FMS were assessed using the Test of Gross Motor Development-Third Edition (TGMD-3), which evaluates two major domains: locomotor skills and object control skills. EF was measured using the Childhood Executive Functioning Inventory (CHEXI), a parent-report scale that includes four subcomponents: working memory, inhibition, regulating ability, and planning ability. Statistical analyses included correlation analysis, and hierarchical regression modeling to examine both overall and stratified associations between FMS and EF by age and sex.ResultsA significant negative correlation was found between fundamental motor skills and executive function, indicating that higher motor skill levels were associated with better EF performance. Age-stratified analyses revealed that this association was significantly stronger in the 3–5 years group compared to the 6–10 years group, demonstrating clear age specificity. Sex-stratified results showed that for boys, the association between object control skills and EF, as well as between inhibition and FMS, was stronger. In contrast, girls exhibited significant associations between locomotor skills and EF, inhibition and FMS, and regulating ability and FMS.ConclusionThis study confirms significant associations between fundamental motor skills and executive function in Chinese children, revealing distinct age-specific and sex-dependent patterns. The findings emphasize the critical importance of implementing targeted motor interventions during key developmental periods, providing both theoretical support and practical guidance for promoting the coordinated development of motor competence and higher-order cognitive functions in children.